Literatur Riview : Perdarahan Postpartum Sebagai Faktor Risiko Utama Terjadinya Anemia Pada Ibu Pascapersalinan - Sukma Ayu; Nur Afrilian Risma; Luthfia Ika Maharani Ilham (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Postpartum hemorrhage is a serious complication that can occur after delivery and is a major cause of maternal morbidity and mortality. This literature review aims to analyze postpartum hemorrhage as a major risk factor for anemia in postpartum mothers. The method used was Systematic Literature Review with a literature research approach using the Google Scholar database. The analysis of eight articles showed that anemia during pregnancy had a significant association with the incidence of postpartum hemorrhage, with a risk of up to 45.7 times greater than mothers without anemia. Other contributing factors included type of delivery, where sectiocaesarea increased the risk of postpartum anemia compared to normal delivery (p=0.004). In conclusion, anemia is a significant risk factor for postpartum hemorrhage that requires early detection, nutritional status monitoring, and comprehensive antenatal care to prevent complications in postpartum women.